2016
DOI: 10.1016/j.clinph.2015.10.038
|View full text |Cite
|
Sign up to set email alerts
|

The effects of working memory on brain–computer interface performance

Abstract: Objective The purpose of the present study is to evaluate the relationship between working memory and BCI performance. Methods Participants took part in two separate sessions. The first session consisted of three computerized tasks. The LSWM was used to measure working memory, the TPVT was used to measure general intelligence, and the DCCS was used to measure executive function, specifically cognitive flexibility. The second session consisted of a P300-based BCI copy-spelling task. Results The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
1
16
1
Order By: Relevance
“…EEG-based BCI strategies have been recently proposed as a promising stroke neurorehabilitation strategy to treat symptoms, including paralysis, cognitive disorders, and aphasia (19)(20)(21)(22)(23)(24)(25). Despite the large heterogeneity in the available literature, there is consensus that BCI-based training can help to improve UL motor function in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…EEG-based BCI strategies have been recently proposed as a promising stroke neurorehabilitation strategy to treat symptoms, including paralysis, cognitive disorders, and aphasia (19)(20)(21)(22)(23)(24)(25). Despite the large heterogeneity in the available literature, there is consensus that BCI-based training can help to improve UL motor function in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…The procedures listed here for evaluating SSVEP-BCI performance can augment other evaluation parameters such as sufficient visual capacity, cognitive status, attention and working memory needed for BCI control (cf. [45,[50][51][52]). Overall, these results reiterate the need for comprehensive physical, sensory and neurological assessment when matching BCI systems to individuals who require AAC (e.g., [9,11]).…”
Section: Resultsmentioning
confidence: 99%
“…Aided AAC devices commonly impose substantial working memory demands (e.g., to locate the target icon and ignore distracting stimuli; Thistle & Wilkinson, 2013), and this is no different for BCI techniques. In addition, prior studies have shown that working memory skills (assessed via the List Sorting Working Memory Task; Gershon et al, 2013) are positively correlated with P300 speller performance in healthy adults (Sprague, McBee, & Sellers, 2016).…”
Section: Medical Considerationsmentioning
confidence: 96%